Model SMEs digital disruption management with business model canvas and integer programming - M. Imron Mas'ud; Abdul Wahid (SAINTIS Publishing, 2022)
The Industrial Era 5.0 and the current covid 19 pandemic have made almost all large, medium, and small companies including MSMEs transform by strengthening their business online to survive and compete, but with the development of technology and intense business competition indirectly many penetrate the market and segments that are not good for other competitors, one of which is the MSME sector for processing products from silkworms in Pasuruan Regency. The purpose of this study is to model the management of digital disruption in SMEs Handicraft processing of silkworm products in Pasuruan Regency through the integration approach of Business Model Canvas (BMC) and integer programming. The results showed that the management of digital disruption of SMEs in the craft of processing products from silkworms requires understanding to be able to optimally utilize online media, especially Facebook, Instagram, and WhatsApp in an effort to market products to create added value and to be created into various types of variations so as to increase the selling price. high with an increase rate of 5% at the beginning of its implementation.